Does the VerifyNow P2Y12 assay overestimate “therapeutic response” to clopidogrel? - Khanna, Vikram; Hobson, Alex; Mikael, Rand; Sambu, Nalyaka; Englyst, Nicola; Curzen, Nick (Thrombosis and Haemostasis, 2014)
In contrast to short thrombelastography (s-TEG) which utilises adenosine diphosphate (ADP) alone, the VerifyNow P2Y12 assay (VN-P2Y12) additionally uses prostaglandin E1 (PGE1) as agonist to assess response to P2Y12 inhibitors. Based upon previous observations, we hypothesised that VN-P2Y12 overestimates the therapeutic effects of clopidogrel. Simultaneous assay with s-TEG and VN-P2Y12 was performed in 43 healthy volunteers and 170 patients either on or off clopidogrel. Furthermore, in 27 patients on clopidogrel 75 mg we compared the effects of adding 22 nM PGE1 to ADP on platelet aggregation in s-TEG to ADP alone. A higher proportion of individuals had a result indicating high platelet reactivity (HPR) with s-TEG than VN-P2Y12 in (i) 43 clopidogrel naïve volunteers (95.3% vs 81.4%, p = NS); (ii) 28 volunteers loaded with clopidogrel 600 mg (39.3% vs 10.7 %, p = < 0.01); (iii) 123 clopidogrel naïve patients (93.5% vs 78%, p = < 0.0001); (iv) 47 patients on clopidogrel 75 mg (42.6% vs 4.3%, p = < 0.0001). In 59 patients loaded with clopidogrel 600 mg/900 mg, a greater proportion had a “therapeutic response” with VN-P2Y12 compared to s-TEG, regardless of the threshold for defining HPR with VN-PY12 (P2Y12 reaction units ≥ 230 or 208). Furthermore, adding PGE1 to ADP in s-TEG potentiated the anti-aggregatory effects of clopidogrel compared with ADP alone. In conclusion, VN-P2Y12 overestimates the functional effects of clopidogrel in some individuals, possibly because it utilises PGE1 in addition to ADP. This could have implications for the ability of VN-P2Y12 to stratify patients as “responders” or “non-responders” to clopidogrel.
Keywords: Clopidogrel; high platelet reactivity; thrombelastography; VerifyNow P2Y12 assay; prostaglandin E1